Advertisement Remove all ads

From the Sum of 3x − Y + 11 and − Y − 11, Subtract 3x − Y − 11. - Mathematics

From the sum of 3x - y + 11 and - y - 11, subtract 3x - y - 11.

Advertisement Remove all ads

Solution

(3x - y + 11) + (- y - 11)

= 3x - y + 11 - y - 11

= 3x - y - y + 11 - 11

= 3x - 2y

(3x - 2y) - (3x - y - 11)

= 3x - 2y - 3x + y + 11

= 3x - 3x - 2y + y + 11

= -y + 11

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 7 Maths
Chapter 12 Algebraic Expressions
Exercise 12.2 | Q 6.1 | Page 240
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×